"The People's Park is bigger, more freely located, more beautiful and – Our own park": Workers, parks, and the spaces of class struggle in turn of the century Norrköping, Sweden. (December 2022) - Jönsson, Erik; Pries, Johan; Mitchell, Don
Engaging with scholarship on hegemony, park history, and in particular with Sevilla-Buitrago's analysis of Central Park as a pedagogical space, this article traces the establishment of two parks in the Swedish textile industry centre of Norrköping. These parks, bearing very similar names – Folkparken and Folkets Park – were established just six years apart. But though both parks linked "park" and "people" ( Folk ), their intended political effects were radically different. The 1895 Folkparken was an elite attempt to create a de-politicised landscape park, while the 1901 Folkets Park was instead the labour movement's attempt to create their own space. Exploring this latter park enables telling a story of park production beyond elite dominance. Like dozens of similar labour-controlled parks across Sweden, the People's Park allowed Norrköping's labour movement to shape their landscape long before the Social Democrats made any significant inroads into parliamentary politics. Combining a platform for socialistic agitation, with a theatre and space for recreation, this park quickly became central to Norrköping's working class. Thereby, it could both enable social-democratic presence at an everyday level, and function as an important resource during periods of intense class-struggle.